Bibliometric Analysis of the Journal Acta Stomatologica Croatica: 2009-2018 - Rebeca Silva de Araújo; Nycolly Vasconcelos Fernandes Porto; Isla Camilla Carvalho Laureano; Lunna Farias; Myroslav Goncharuk-Khomyn; Alessandro Leite Cavalcanti; Alidianne Fábia Cabral Cavalcanti (University of Zagreb. School of Dental Medicine, 2020)
Objective: To analyze a bibliometric profile of scientific production published in Acta Stomatologica Croatica (ASCRO). Material and methods: Scientific papers published from March 2009 to December2018 were analyzed. Information on the year of publication was collected by four trained examiners. Dentistry area, study type and design, data analysis method, presence of randomization, number of authors and corresponding author affiliation were investigated. Data were analyzed descriptive statistics. Results: A total of 328 articles were evaluated, with a predominance of research in the field of Dental Materials (16.5%), with original article being the most frequent (74.1%). Observational studies accounted for 52.4%, using inferential statistics (83.2%) and non-randomized experimental studies (66.1%). Cross-sectional studies were more common in areas of Behavioral, Epidemiologic & Health Services Research (86.3%), case reports in Craniofacial Biology (54.0%) and Oral Health Research (53.1%), while in vitro studies were more common in the areas of Dental Materials (90.7%),Microbiology / Immunology (70.0%) and Cariology Research (66.7%). Most articles were written by four authors (24.1%), while foreign affiliation was observed in 53.0% of studies. Conclusion: The profile of ASCRO scientific production shows a predominance of original studies carried out in the are as of Dental Materials and Behavioral, Epidemiologic & Health Services Research, with growing participation of foreign researchers.